SAMPLING AUDIT OF THE TAX AUDIT IN INDONESIA: A LEGAL CERTAINTY PERSPECTIVE - Denny Irawan (Scientium Law Review (SLR), 2022)
The problems of low Audit Coverage Ratio (ACR) and Additional Underpaid Tax Assessment Letters (SKPKBT), tax audit period, and tax determination expiration considerations indicate that this phenomenon is necessary to produce an ideal (legal) concept related to audit sampling in tax audits for Indonesia. Based on the normative juridical method, it was concluded that there is a need for legal certainty related to audit sampling based on the constitutional order in connection with the fulfillment of tax law requirements as a lex specialist derogat lex generalist. The absence of audit sampling provisions in tax audits is based on the absence of statutory regulations binding on taxpayers, tax authorities, and certain third parties. In fact, there is always uncertainty in tax audits, there is a need for sufficient legal evidence in tax audits, there is a need to consider efficiency and economic benefits in carrying out tax audits, there is a need to use the means of professional judgment of tax examiners, and a reasonable basis is needed to conclude the characteristics of a population in a tax audit.